Perceptions of Biology Department Students, State University of Gorontalo On Online Learning During the Covid 19 Pandemic - Della safitri Mamonto; Hartono D Mamu; Djuna Lamondo (Jurnal Pendidikan Biologi, 2022)
The research aims to determine the perceptions of Biology Department studenst at Universitas Negeri Gorontalo towards online learning during the Covid-19 pandemic. This research employs a survey method, and data are collected through a questionnaire. The research participants are all students majoring in Biology who were affected by the Covid-19 pandemic from 2018 to 2021, totaling 420 participants. The sample is determined by using stratified random sampling with 15% in each year totaling 67 participants as the sample. The results indicate that: (1) the lecturer capability indicators are in the very good category with 84%; (2) indicators of learning activities are in the good category with 83.7%; (3) the indicators of facilities and infrasructure are in the good category with 85.3%; (4) The average of all indicators indicate that perception of students majoring in Biology at Universitas Negeri Gorontalo towards online learning during the covid-19 pandemic are in the very good category with 84.3%.